2023
DOI: 10.3390/ijms24044100
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Responses of Daphnids to Chronic Exposures to Pharmaceuticals

Abstract: Pharmaceutical compounds are among several classes of contaminants of emerging concern, such as pesticides, heavy metals and personal care products, all of which are a major concern for aquatic ecosystems. The hazards posed by the presence of pharmaceutical is one which affects both freshwater organisms and human health—via non-target effects and by the contamination of drinking water sources. The molecular and phenotypic alterations of five pharmaceuticals which are commonly present in the aquatic environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…37,38 Specically, acute and chronic exposure of Daphnia magna to metformin decreased the activity of various enzymes of the metabolism 25 and increased the activity of several detoxication enzymes, respectively. 39 The concentrations of pollutants tested in the developed feeding assay were notably lower compared to the effective concentrations reported in previous studies. This nding serves as compelling evidence for the high sensitivity of the method.…”
Section: The Impact Of Pollutants On the Feeding Of Daphnidsmentioning
confidence: 63%
“…37,38 Specically, acute and chronic exposure of Daphnia magna to metformin decreased the activity of various enzymes of the metabolism 25 and increased the activity of several detoxication enzymes, respectively. 39 The concentrations of pollutants tested in the developed feeding assay were notably lower compared to the effective concentrations reported in previous studies. This nding serves as compelling evidence for the high sensitivity of the method.…”
Section: The Impact Of Pollutants On the Feeding Of Daphnidsmentioning
confidence: 63%
“…Given the scarcity of research on the effects of indomethacin and ibuprofen on freshwater organisms, particularly D. magna, our study aimed to highlight their significance while also introducing additional markers of physiology other than mortality, growth, and reproduction rate as common endpoints. We recently demonstrated that markers related to physiology and enzymatic activity, in addition to metabolic perturbations, are useful endpoints for pollution assessment [28,30]. It is worth noting that this is the first reference of indomethacin, ibuprofen, and daphnids using additional molecular markers rather than using only toxicity results.…”
Section: Discussionmentioning
confidence: 97%
“…Daphnids were cultured under a 16 h:8 h of light:dark photoperiod at 20 • C in OECD media (final concentrations 0.29 g CaCl 2 •2H 2 O/L, 0.123 g MgSO 4 •7H 2 O/L, 0.065 g NaHCO 3 /L, 0.0058 g KCl/L, 2 µg Na 2 SeO 3 /L, pH 7.7) [28]. Indomethacin and ibuprofen were dissolved in DMSO, which had a final concentration of 0.005% v/v in the exposure, which is within the concentration range used in previous studies [27,29,30]. Neonates (<24 h) were collected from the third brood of their mothers and used for experiments.…”
Section: Culturing Of Daphnids and Acute Toxicitymentioning
confidence: 89%
See 1 more Smart Citation
“…This property is commonly employed in fixation, lethality, and reproductive tests [45,46]. D. magna has been used to study the short-or long-term effects of pollutants such as nanoparticles [47,48], pharmaceuticals [49], metals [50], and pesticides [51]. Moreover, studies on the effects of combined pollutants on D. magna have received wide attention [52,53].…”
Section: Introductionmentioning
confidence: 99%